Implementation of the Strengthening the Pancasila Student Profile Project (P5) on Character Development of Elementary School Students - Toni Norman Hanafi; Ahmad Rifandi (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2025)
This study aims to explore how the Strengthening the Pancasila Student Profile Project (P5) is implemented and the extent of its influence on character development among elementary school students. The research focused on two schools in Bandung Regency, namely SDN Cingcin 1 Soreang and SDN Majalaya 05, which have adopted the P5 project under the framework of the Merdeka Curriculum. A qualitative descriptive approach was employed, with data collected through observations, interviews, document analysis, and questionnaires. The participants of this study included teachers, students, and school principals. The findings revealed that the implementation of the P5 project at both schools consisted of three main stages: project planning based on local themes, the execution of collaborative activities, and reflective evaluation. These project activities made significant contributions to fostering the six-character dimensions of the Pancasila Student Profile, particularly in cultivating independence, collaboration, tolerance, and environmental awareness. Nevertheless, several obstacles were identified, such as teachers’ limited understanding of the P5 concept and insufficient supporting facilities for project implementation. Overall, the P5 project has proven to be an effective approach for instilling character values in elementary school students. Therefore, this study recommends improving teachers’ competencies and strengthening collaboration between schools and communities to optimize the implementation of the P5 project.